Knockdown of tropomyosin‐related kinase B receptor expression in the nucleus accumbens shell prevents intermittent social defeat stress‐induced cross‐sensitization to amphetamine in rats. (19th December 2013) - Wang, Junshi; Bina, Robert W.; Wingard, Jeffrey C.; Terwilliger, Ernest F.; Hammer, Ronald P.; Nikulina, Ella M.
Abstract: The nucleus accumbens (NAc) is a critical brain region for the rewarding effects of drugs of abuse. Brain‐derived neurotrophic factor (BDNF) can facilitate stress‐ and drug‐induced neuroadaptation in the mesocorticolimbic system. BDNF‐containing projections to the NAc originate from the ventral tegmental area (VTA) and the prefrontal cortex, and BDNF release activates tropomyosin‐related kinase B (TrkB). In this study, we examined the necessity for BDNF‐TrkB signaling in the NAc shell during social defeat stress‐induced cross‐sensitization to amphetamine. Adeno‐associated virus expressing short hairpin RNA directed against TrkB (AAV‐shTrkB) was infused bilaterally into the NAc shell to knock down TrkB, whereas AAV‐GFP (green fluorescent protein) was used as the control virus. Rats were exposed to intermittent social defeat stress or handling procedures; amphetamine challenge was given at 10 days after the last defeat and locomotor activity was measured. Stressed rats that received the control virus showed cross‐sensitization to amphetamine compared with the handled rats. In contrast, NAc TrkB knockdown prevented social defeat stress‐induced cross‐sensitization. TrkB knockdown in the NAc was found to reduce the level of phospho‐extracellular signal‐regulated kinase 1 in this region. NAc TrkB knockdown also prevented stress‐induced elevation of BDNF and the glutamate receptor type 1 (GluA1) subunit of AMPA receptor in the VTA, as well as ΔFosB expression in the NAc. These findings indicated that BDNF‐TrkB signaling in the NAc shell was required for social defeat stress‐induced cross‐sensitization. NAc TrkB‐BDNF signaling also appeared to be involved in the regulation of GluA1 in the VTA, as well as in the NAc ΔFosB accumulation that could trigger cross‐sensitization after social defeat stress. Abstract : We demonstrated in rats that BDNF‐TrkB signaling in the nucleus acuumbens (NAc) shell is the prerequisite factor of the neuroplasticity in mesolimbic circuitry required for social defeat stress‐induced cross‐sensitization to amphetamine. We found that viral vector‐mediated TrkB knockdown in the NAc shell prevented social defeat stress‐induced cross‐sensitization to amphetamine. Also stress‐induced ΔFosB accumulation in the NAc, the elevation of BDNF and GluA1 subunit of AMPAR in the ventral tegmental area were prevented by intra‐NAc shell TrkB knockdown.